An ethnomethodological analysis of students’ understanding of the concept of trigonometry in a high-stakes examination in South Africa - Marius Derick Simons; Kadek Adi Wibawa (Beta: Jurnal Tadris Matematika, 2021)
[English]: In South Africa, National Senior Certificate (NSC) mathematics examination is a capping external examination taken at the culmination of twelve years of schooling. The purpose of this study was to investigate and analyze the responses of examinees in the examinations in the concept of trigonometry. While the study mainly used an ethnomethodological approach, a documentary analytical approach was also adopted. Documentary analysis was necessitated by the private nature of the NSC examination, as we only had access to the written work of the examinees. The major findings were: (1) that the strategies and tactics used by examinees are highly driven by the context of the high-stakes examination; (2) that examinees’ ways of working exhibit the general structure of the practice that is commonly found in mathematical discourse practices. Further studies are required to deepen the understanding of the thinking processes of examinees by conducting focus group interviews, where the examinees are afforded opportunities to explain their workings in school-based assessments. [Bahasa]: Di Afrika Selatan, ujian matematika National Senior Certificate (NSC) adalah ujian tambahan yang diambil pada akhir dari dua belas tahun sekolah. Penelitian ini bertujuan untuk melakukan investigasi dan analisis tanggapan siswa peserta ujian matematika NSC terkait konsep trigonometri. Selain pendekatan etnometodologi yang secara umum dipakai dalam penelitian ini, pendekatan analitis dokumenter yang juga diadopsi terkait karakteristik ujian NSC, dalam hal inipeneliti hanya memiliki akses pada jawaban tertulis peserta ujian. Temuan utama penelitian adalah: (1) bahwa strategi dan taktik yang digunakan oleh peserta ujian sangat didorong oleh konteks ujian berisiko tinggi; (2) bahwa cara kerja peserta ujian menunjukkan struktur umum praktik yang biasa ditemukan dalam praktis diskursus matematika. Penelitian lebih lanjut diperlukan untuk memperdalam pemahaman tentang proses berpikir peserta ujian dengan melakukan wawancara kelompok terfokus, dimana peserta ujian diberikan kesempatan untuk menjelaskan cara kerja mereka dalam penilaian berbasis sekolah.